O positivismo jurídico como fundamento da educação do bacharel em direito: a concepção do objeto como condicionante do modo de ensino. - Mesquita, Márcio Satalino (2005)
Starting from the idea that the philosophical law conception accepted, consciously or unconsciously, determines, or at least conditiones significantly, the law teaching, the author examines the legal acts that rules the law schools curriculum directives in Brazil, as well as the educational programs and some courses descriptions of law graduation at the USP Universidade de São Paulo Law School and FADISC Faculdades Integradas de São Carlos Law School, and questions of some admission examinations of Ordem dos Advogados do Brasil, Seção de São Paulo (Brazil s Bar Association, Section of São Paulo). This analysis, which includes an examination of accepted bibliography references and other teaching practices, is done aiming at the identification of the determinations or conditionings of legal positivism accepted as the predominant philosophical law conception in Brazil about the teaching way. Towards, the author describes the legal positivism concept and identifies its main characteristics, mainly its more sophisticated version, using the Hans KELSEN s work, specially referring to the distinguishing between Natural Law and Positive Law, as well as referring to the supremacy of statute as law source and about its hermeneutics peculiarities. The author makes an effort to establishes distinguishings and similarities between legal positivism and Auguste COMTE s positivism, as well as between legal positivism and neo-positivism. The issue of the practicability of a juridical science understood as the currently dominant paradigm and as relevant legal positivism characteristic is treated by the author incidentally, making criticisms about objective verifiability of legal rules, about legal or illegal human behaviors; about the possibility of legal logics development; and about the juridical science object delimitation, based on the Karl POPPER s empiric science concept. For the criticism of the juridical science object delimitation, in the conception of the legal positivism, the author develops, as a category of analysis, the statute fetishism concept, based on Karl MARX s commodity fetishism concept. Throughout the examination of the mentioned empiric data, including comparative analysis with statute texts, the author establishes the characteristics of the so called Positivist Law Teaching, about curriculum directives, the way of making the curriculum, the courses contents, the doctrine and the evaluation way. Finally, the author indicates the consequences of positivist law teaching, concerning to normative reductionism, normative abstractionism, non-historicism, and legal technicism, and proposes a new approach of law teaching, about the abandoning of scientific paradigm, and about the enlargement of the study object limits.